SECURING INTEGRATED TRANSPORTATION NETWORKS - Gordon, Gary A.; Young, Richard R. (Elsevier, 2024)
This book provides a comprehensive look at multimodal transportation security-its dynamics, evolving threats, and technology advances that enhance operational security and related infrastructure protection and hardening, as well as the regulatory environment. As threats are evolving, so is the technology used in enhancing transportation security, operational procedures, and regulations. This book addresses this dynamic evolution of transportation security, serving as a primary reference for information on the range of activities and components involved in transportation security. It covers the myriad parts involved in the relationship between, and among, logistics, the supply chains and transportation entities, and more. In addition, it looks at operations, infrastructure, equipment, laws and regulations, policies and procedures, and risk focused on transportation safety and security by mode and transportation in general. Cooperation and partnering with and among the industry, to include transportation providers and government agencies, is the way forward to ensure that security is maintained and keeps pace with the evolving threat and regulatory landscape.